The Removal of Ear Trophies Associated with Scalpings in Prehistoric North Alabama. (15th May 2014) - De Vore, W. E.; Jacobi, K. P.
Abstract: The act of scalping has long been associated with Native American conflict‐related human body part trophy taking. Reasons for their removal were varied and often included communal and personal factors. Previous research has identified several different types of scalp removals based on the amount of soft tissue affected during the process of scalping. One of these types can involve the removal of the ears. Through reanalysis of known scalping victims within the middle Tennessee Valley of North Alabama, we have identified five cases where victims were both scalped and had their ears removed. These cases provide a unique understanding of the practice of human body part trophy taking. They support ethnographic accounts that indicate ear removal has great time depth and was geographically widespread. Although the five cases presented here are similar to total compound scalpings, they actually represent total simple scalpings. Unlike total compound scalpings, where the ears are removed attached to the skin of the scalp, these cases show evidence of secondary removal of the ears after the scalp was already detached. This secondary removal of the ears after the act of scalping supports the interpretation that the aggressors intended different purposes for each trophy. It is likely that the scalp and ears each had their own meaning. Copyright © 2014 John Wiley & Sons, Ltd.